Formulation, cellular uptake and cytotoxicity of thymoquinone-loaded PLGA nanoparticles in malignant melanoma cancer cells - Ibrahim, Wisam Nabeel; Mohd Rosli, Luqman Muizzuddin; Abd Almonem, Doolaanea (Dove Medical Press, 2020)
Introduction: Thymoquinone (TQ) is the main active compound extracted from Nigella sativa a traditional herb with wide therapeutic applications and recognizable anticancer properties. This study aimed to formulate and characterize TQ-nanoparticles using PLGA as a biocompatible coating material (TQ-PLGA NPs) with the evaluation of its therapeutic properties in human melanoma cancer cells. Methods: The TQ-PLGA NPs were prepared and characterized for size, zeta potential, encapsulation efficiency, and release profile. Results: The particle size was 147.2 nm, with 22.1 positive zeta potential and 96.8% encapsulation efficiency. The NPs released 45.6% of the encapsulated TQ within 3 h followed by characteristic sustained release over 7 days with a total of 69.7% cumulative release. TQ-PLGA NPs were taken up effectively by the cells in a time-dependent manner up to 24 h. Higher cell toxicity was determined within the first 24 h in melanoma cells due to the rapid release of TQ from the NPs and its low stability in the cell culture media. Conclusion: TQ-PLGA NPs is a potential anticancer agent taking advantage of the sustained release and tailored size that allows accumulation in the cancer tissue by the enhanced permeability and retention effect. However, stability problems of the active ingredient were address in this study and requires further investigation.